Development of psychological and educational aspects of interaction between medical workers and patients - T. V. Ryabova; A. A. Mutigullina (Кардиоваскулярная терапия и профилактика)
Aim. To develop a patient education algorithm used by medical workers. The leading method for studying this problem is a pedagogical experiment, as well as a statistical processing of quantitative research results. The relevance of this study is due to the need to address the priorities of the Healthcare national project, i.e. developing the skills of maintaining a healthy lifestyle among the population, changing behavior and attitudes towards their own health and the health of others. The introduction of educational programs for patients in combination with therapeutic measures contributes to the most complete rehabilitation. Forming partnerships and trust between patients and medical workers to prevent diseases requires the latter to have psychological and pedagogical knowledge and skills.Material and methods. The study was conducted on the basis of the City Outpatient Clinic № 7 (Kazan). The study was conducted in the Department of Internal Medicine on the daytime basis. The experiment involved 20 nurses, 15 doctors and 60 patients from these departments. The study was carried out in three following stages: at the first stage, the current state of the problem under study in pedagogical theory and practice was analyzed, a research methodology program was developed, and a survey of nurses at the medical institution was conducted. At the second stage, the theoretical concept of the study was adjusted, a training experiment was conducted with doctors and senior nurses, and a structural and functional model of pedagogical training of medical workers for patient education was introduced. At the third stage, analysis, generalization and systematization of the data obtained, and presentation of the research results were carried out.Results. The developed educational program for teaching patients, consisting of three stages (design, implementation, control of the educative process), and containing various methods of training, contributes to the formation of the psychological and pedagogical competence of medical workers. The specificity of the methodology is that the emphasis is on developing the ability to present information in an accessible form, and, most importantly, teach the patient and his family members specific techniques for self-monitoring, self-care and self-help.Conclusion. The study proved the effectiveness of the proposed algorithm for teaching patients by medical workers, which was confirmed by the development of patients’ skills and abilities in selfmonitoring and self-help. Patients' behavioral habits have changed, their motivation to improve their health has increased, and they have become responsible for their health.